Finding missing markets (and a disturbing epilogue): evidence from an export crop adoption and marketing intervention in Kenya - Nava Ashraf; Xavier Giné; Dean S. Karlan (Yale University, Economic Growth Center, 2008)
In much of the developing world, many farmers grow crops for local or personal consumption despite export options which appear to be more profitable. Thus many conjecture that one or several markets are missing. We report here on a randomized controlled trial conducted by DrumNet in Kenya that attempts to help farmers adopt and market export crops. DrumNet provides smallholder farmers with information about how to switch to export crops, makes inkind loans for the purchase of the agricultural inputs, and provides marketing services by facilitating the transaction with exporters. The experimental evaluation design randomly assigns pre-existing farmer self-help groups to one of three groups: (1) a treatment group that receives all DrumNet services, (2) a treatment group that receives all DrumNet services except credit, or (3) a control group. After one year, DrumNet services led to an increase in production of export oriented crops and lower marketing costs; this translated into household income gains for new adopters. However, one year after the study ended, the exporter refused to continue buying the cash crops from the farmers because the conditions of the farms did not satisfy European export requirements. DrumNet collapsed in this region as farmers were forced to sell to middlemen and defaulted on their loans. The risk of such events may explain, at least partly, why many seemingly more profitable export crops are not adopted.
Keywords: O12; Q17; F13; 330; Field experiment; export crop; food safety standards; Landwirtschaft; Getreideanbau; Subsistenzwirtschaft; Außenhandelsförderung; Produktivität; Feldforschung; Kenia